A mysterious little piece: A compound-weave textile incorporating sea silk from the Natural History Museum, London - Maeder, Felicitas; Rogers, Penelope Walton; Gleba, Margarita (Archaeological Textiles Review, 2019)
Sea silk, derived from the beard of the Pinna nobilis clam, has often been described in historical sources, but only rarely identified scientifically in extant textiles. This paper describes the microscopy of the fibres in a textile held in the Cuming Collection at the Natural History Museum in London. The textile is a compound weave that incorporates yarns made of sea silk, ordinary cultivated silk and a fine animal coat fibre. The fibres were identified by a combination of transmitted-light, polarised-light and scanning electron microscopy. There is little documentation concerning the origin of the piece, but it is likely to be18th-century Italian and may have come from a waistcoat.